PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENGUNJUNG PADA WISATA AGRO TAMBI KECAMATAN KEJAJAR KABUPATEN WONOSOBO - Vita Aulia Fatmawati; Ignatius Suprih Sudrajat (Fakultas Pertanian UST, 2018)
Quality of service plays an important role in shaping customer satisfaction, besides that it’s closely related to creating profits for the company. The study aims to determine the effect of service quality with indicators of reliability, responsiveness, assurance, empathy and tangibles of the satisfaction of visitors to Wisata Agro Tambi.The research method uses descriptive and causal research with a quantitative approach. The research sample amounted to 39 taken using accidental sampling technique. The time of the study was conducted from April to May 2018. The results showed that the variables of reliability, assurance, empathy and tangibles had a positive and significant influence while the responsiveness had a negative and significant effect on visitor satisfaction.Quality of service plays an important role in shaping customer satisfaction, besides that it’s closely related to creating profits for the company. The study aims to determine the effect of service quality with indicators of reliability, responsiveness, assurance, empathy and tangibles of the satisfaction of visitors to Wisata Agro Tambi.The research method uses descriptive and causal research with a quantitative approach. The research sample amounted to 39 taken using accidental sampling technique. The time of the study was conducted from April to May 2018. The results showed that the variables of reliability, assurance, empathy and tangibles had a positive and significant influence while the responsiveness had a negative and significant effect on visitor satisfaction.